Analysis of numerical schemes in collocated and staggered grids for problems of poroelasticity - Ferreira, Carlos Augusto Soares (2019)
Dissertação (mestrado) - Universidade Federal de Santa Catarina, Centro Tecnológico, Programa de Pós-Graduação em Engenharia Mecânica, Florianópolis, 2019.